Investigation of the dynamical structures for nonlinear Vakhnenko-Parkes equation using two integration schemes - Arshed, Saima; Akram, Ghazala; Sadaf, Maasoomah; Hussain, Ejaz; Abbas, Muhammad; Alzaidi, Ahmed S. M.; Riaz, Muhammad Bilal (Optical and quantum electronics, 2024)
The dynamic behavior of the Vakhnenko-Parkes equation is examined in this manuscript. This is an important subject because of its implications for comprehending intricate mathematical models describing traveling wave phenomena and solitons. The construction of traveling wave solutions for the Vakhnenko-Parkes equation in closed form is the main issue addressed in the study. The modified auxiliary equation approach and the extended ( G ′ G 2 ) -expansion method are used to address this because they are effective in producing precise solutions of a large class of nonlinear partial differential equations. A visual component to comprehending the behavior of the equation is added by employing 3 D -surface graphs, 2 D -line graphs, and contour plots to explore these solutions graphically. A variety of traveling wave behavior is observed from the obtained solutions. These results imply that the Vakhnenko-Parkes equation and its solutions are complex, offering important insights into the underlying dynamics. The proposed techniques are applied for the first time to study the considered model in this work. A comparison of the obtained results with the previous works is presented to confirm the significance and novelty of the reported results.